2014
DOI: 10.1161/circoutcomes.113.000698
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Characteristics With Cardiovascular Health in the Multi-Ethnic Study of Atherosclerosis

Abstract: Background The concept of ‘cardiovascular health’ (CVH) was introduced as a global measure of one’s cardiovascular health. Previous studies established the relationship between neighborhood characteristics and individual cardiovascular risk factors. However, the relationship between neighborhood environment and overall CVH remains unknown. Methods and Results We analyzed data from the MESA baseline exam (2000–2002). Mean age was 61.6 years and 52% were female. Ideal, intermediate and poor categories of chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 36 publications
4
143
5
Order By: Relevance
“…Historical policies of social exclusion as well as documented discrimination in access to health‐enhancing resources experienced by racial/ethnic minority groups in the United States are likely contributors to racial/ethnic differences in CVH 16, 17, 18. For example, neighborhoods with a higher percentage of racial/ethnic minority residents—regardless of income—have fewer grocery stores,19 fewer recreation facilities,20 and less walkability21; these neighborhood resources have been linked to preservation of ideal CVH 22. Previous research has shown that individuals who have multiple forms of social disadvantage—such as low income, low education, and nonwhite race—are even less likely to have ideal CVH 11.…”
Section: Discussionmentioning
confidence: 99%
“…Historical policies of social exclusion as well as documented discrimination in access to health‐enhancing resources experienced by racial/ethnic minority groups in the United States are likely contributors to racial/ethnic differences in CVH 16, 17, 18. For example, neighborhoods with a higher percentage of racial/ethnic minority residents—regardless of income—have fewer grocery stores,19 fewer recreation facilities,20 and less walkability21; these neighborhood resources have been linked to preservation of ideal CVH 22. Previous research has shown that individuals who have multiple forms of social disadvantage—such as low income, low education, and nonwhite race—are even less likely to have ideal CVH 11.…”
Section: Discussionmentioning
confidence: 99%
“…We categorized the LS7 metrics into ideal, intermediate, and poor with modifications as previously reported in MESA (Table S1). 7, 28 We created the LS7 score from points assigned to each category of the metrics; poor=0 point, intermediate=1 point, and ideal=2 points. The points were summed for a total LS7 score ranging from 0 to 14 29.…”
Section: Methodsmentioning
confidence: 99%
“…The points were summed for a total LS7 score ranging from 0 to 14 29. As previously described, we considered 0 to 8, 9 to 10, and 11 to 14 points as inadequate, average, and optimal scores, respectively 28. The HF incidence rate per 1000 person‐years was calculated for each ideal metric and LS7 score category stratified by race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants who scored 0 to 8 points were classified as inadequate, those who scored 9 or 10 points were classified as average, and participants who scored 11 to 14 points were classified as optimal 21. Table S1 presents the proportion of MESA participants who fall into each category of the metrics.…”
Section: Methodsmentioning
confidence: 99%